The Challenge of Bureaucratic Neutrality in the 2024 Legislative and Presidential Elections in Indonesia - Kamaluddin, Kamaluddin; Haeril, Haeril; Hidayatullah, Arief (Jurnal Studi Ilmu Pemerintahan, 2024)
This study examines the intricate challenges of maintaining bureaucratic impartiality in the 2024 Legislative and Presidential Elections in Bima Regency, particularly emphasizing the pervasive influence of political dynasties. This research employs a descriptive qualitative approach and an in-depth literature review to elucidate the intricacies of local political dynamics. It illuminates how political pressure, interest-based interventions, and entrenched polarization erode bureaucratic integrity. The findings illustrate the considerable influence wielded by political dynasties in Bima Regency, which extends beyond the political sphere to encompass symbolic, cultural, and economic domains. This formidable sway presents a formidable challenge to the neutrality of bureaucratic institutions during the electoral process. Furthermore, this research highlights the crucial function of independent media in advancing inclusive democracy and upholding bureaucratic impartiality. By offering a nuanced analysis, the research uncovers the challenges and provides strategic recommendations to improve bureaucratic independence. Some key suggestions include improving ethics education and training for civil servants, strengthening oversight mechanisms, enforcing strict sanctions against violations, and encouraging greater public engagement and awareness. Ultimately, this study contributes valuable insights to ongoing efforts to improve the quality of democracy in Bima District and across Indonesia, paving the way for more resilient and transparent democratic processes in the future.